2016
DOI: 10.1631/jzus.b1600096
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure balloon dilation for male anterior urethral stricture: single-center experience

Abstract: Abstract:Objectives: We retrospectively reviewed the urethral stricture cases treated in our tertiary center, and assessed the safety and feasibility of the high-pressure balloon dilation (HPBD) technique for anterior urethral stricture. Methods: From January 2009 to December 2012, a total of 31 patients with anterior urethral strictures underwent HPBD at our center, while another 25 cases were treated by direct vision internal urethrotomy (DVIU). Patient demographics, stricture characteristics, surgical techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…The low complication rate is likely related to the mechanism of BD, which applies radial force to strictures under direct vision and is generally less traumatic with a lower bleeding risk and infection rate compared to blind sequential dilation or DVIU [ 10 ]. One study directly comparing BD to DVIU revealed shorter operative times and lower complication rates with BD [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The low complication rate is likely related to the mechanism of BD, which applies radial force to strictures under direct vision and is generally less traumatic with a lower bleeding risk and infection rate compared to blind sequential dilation or DVIU [ 10 ]. One study directly comparing BD to DVIU revealed shorter operative times and lower complication rates with BD [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our logistic regression analysis revealed three factors that were associated with variations in GBS: premature rupture of membranes was identified as a risk factor, and the other two factors were found to be protective factors. Perhaps the bacteria involved in gravida urinary tract infections have a competitive relationship with GBS and other bacteria (Yu et al, 2016). To our knowledge, the low GBS infection rate of premature neonates has not been previously reported.…”
mentioning
confidence: 79%
“…Methods for mechanical disruption of urethral stricture include balloon dilation, DVIU and sequential dilation using urethral sounds 20,21 . Although some surgeons prefer DVIU given the ability to directly visualize the stricture at time of dilation, both balloon dilation and rigid dilators have been shown to outperform DVIU with respect to long‐term retreatment rate 21–23 . Concerns regarding poor placement of the balloon during dilation may be obviated either by performing balloon dilation under direct vision or by using intra‐operative fluoroscopy for stricture localization 21,24,25 .…”
Section: Discussionmentioning
confidence: 99%